EVOLUSI TEORI KETERGANTUNGAN SISTEM MEDIA MENJADI TEORI INFRASTRUKTUR KOMUNIKASI - Dede Mahmudah (BPSDMP Kominfo Jakarta, 2011)
This article deals with a matter of evolution theory in the study of science communications. Object of theory discussed is Media System Dependency Theory which introduced by Ball-Rokeach. This article is focused to overview: 1). History of Media System Dependency Theory emergence. 2) Development phase of this theory; 3). Challenge for this MSD theory: Critique and Change of Time, and 4). From MSD toward Communication Infrastructure Theory (CIT).Artikel ini mencoba membahas persoalan evolusi teori dalam studi ilmu komunikasi. Teori yang dijadikan objek bahasan adalah teori ketergantungan sistem media (MSD) dari Ball-Rokeach. Fokus persoalan yang dibahas dalam tulisan ini mencakup : 1) Riwayat Kemunculan Teori MSD; 2) Fase Perkembangan Teori MSD 3) Tantangan terhadap teori MSD: Kritik dan Perubahan Waktu dan 4) Dari MSD Menuju Communication Infrastructure Theory (CIT).